2020
DOI: 10.3102/0013189x20978806
|View full text |Cite
|
Sign up to set email alerts
|

Distance Learning and Parental Mental Health During COVID-19

Abstract: As COVID-19 cases continue to increase across the country, there is a concern about the extent to which this pandemic will affect students. Since March 2020, schools transitioned to a distance-learning format, which unintentionally forced parents into new teaching roles as proxy educators. In this brief, we explore the association between distance learning and the mental health of proxy educators. We find that parents with children who struggled with distance learning experienced elevated mental distress. Give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(119 citation statements)
references
References 6 publications
3
110
1
2
Order By: Relevance
“…103 New research conducted during COVID-19 showed that approximately half of parents with children learning remotely had at least one child struggling with distance learning, which in turn was associated with higher parental stress. 104 Results from Statistics Canada crowdsourcing initiatives show that among participants, youth, recent immigrants, certain groups designated as visible minorities, gender diverse people, and Indigenous people, were also more likely to report symptoms consistent with moderate or severe generalized anxiety. 105 Data from Statistics Canada highlight that stress on families is unequally distributed.…”
Section: Impacts and Social And Family Contextmentioning
confidence: 99%
“…103 New research conducted during COVID-19 showed that approximately half of parents with children learning remotely had at least one child struggling with distance learning, which in turn was associated with higher parental stress. 104 Results from Statistics Canada crowdsourcing initiatives show that among participants, youth, recent immigrants, certain groups designated as visible minorities, gender diverse people, and Indigenous people, were also more likely to report symptoms consistent with moderate or severe generalized anxiety. 105 Data from Statistics Canada highlight that stress on families is unequally distributed.…”
Section: Impacts and Social And Family Contextmentioning
confidence: 99%
“…Parents can be instrumental in reducing screen time for children by ameliorating the overall environment of the house, improving family bonding, and regulating screen time. Although parents' role has become more critical during this COVID-19 pandemic, many are struggling to achieve a work-life balance as they must navigate working from home [45][46][47] . This struggle is more pronounced in lower-income families as they were hit disproportionately by the current catastrophe 48 .…”
Section: Mitigating Adverse Health Outcomes Associated With Screen Timentioning
confidence: 99%
“…Differences between parents' own mathematics education (which for many emphasized rules and procedures [11]) and the curriculum and instruction experienced by their children present barriers to parental involvement [16], and this challenge was only intensified by COVID-19. Parents and children alike experienced increased anxiety during emergency remote instruction [37,47], and likely even more so in mathematics. For example, consider these memes from our initial exploratory data generation (Figure 7), which show parents' frustration with supporting their children with unfamiliar problem-solving approaches.…”
Section: Renewing To Efforts To Engage Parentsmentioning
confidence: 99%